The family processes from the optics of access to justice: towards the consolidation of family procedural law - Celis Vásquez, Marco Antonio (2020)
Family Procedural Law has been consolidated in the last decade as scholar doctrinary opinions have acknowledged its own characteristics and peculiarities, and the existence of self-governing principles, as well as the requirement to have a judge specialized in this kind of proceedings, with a legal-technical training in family matters, and with a perspective different from the other civil actions. It is important to point out Rogelio Llerena Quevedo’s view as to the role of a judge. He states that: «an unbiased judge interpreting and administering justice could only be taken as one of the best human being. This implies that even if he is the best, he is still human, and therefore, capable of making mistakes. Based on those reasons, there should always be a Code of Ethics as a guide for a good judge».